Comment les politiques d’urbanisation se traduisent-elles dans le paysage urbain : une approche par les métriques spatiales - Nathalie Long; Thomas Leveiller (VertigO)
This study is included in a larger scientific project to analyse land cover changes in the region Ile-de-France. Proving a contrasting change between inner and outer suburbs, the actual tendency is towards the growth of urban areas to the detriment of rural areas. The five “villes nouvelles” (Cergy-Pontoise, Évry, Marne-la-Vallée, Sénart, Saint-Quentin-en-Yvelines), result of a strong urban policy since the 60’s, created to equilibrate the regional development, are characterized by specific urban profiles and spatial organizations, compared to others cities where urban sprawl has followed the main trend of urbanization, after the Second World War (multiple dwellings construction and then individual housing). From an urban planning point of view, a comparison between the new city of Évry and the city of Longjumeau, outer suburb’s city, characterized by rural areas disappearance in favour of individual housing, is proposed. This case study is based on computation of spatial metrics allowing a characterization of urban landscapes (irregularity and fragmented shapes, compactness or density of urban areas). This analyse reveals different urban landscapes between these territories, at the town scale and at the district scale. The urban policies, since 45 years, are expressed through specific urban landscapes in new cities. Indeed, Évry presents an urban landscape more fragmented and complex than Longjumeau, even if some areas are exceptions, like the irregularity of individual housing’s area in Longjumeau.